2017
DOI: 10.1002/2016jd026315
|View full text |Cite
|
Sign up to set email alerts
|

Airborne measurements of western U.S. wildfire emissions: Comparison with prescribed burning and air quality implications

Abstract: Wildfires emit significant amounts of pollutants that degrade air quality. Plumes from three wildfires in the western U.S. were measured from aircraft during the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC4RS) and the Biomass Burning Observation Project (BBOP), both in summer 2013. This study reports an extensive set of emission factors (EFs) for over 80 gases and 5 components of submicron particulate matter (PM1) from these temperate wildfires. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
264
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 242 publications
(320 citation statements)
references
References 139 publications
(307 reference statements)
33
264
2
Order By: Relevance
“…Many of the above species have EFs that agree between PTR-ToF and FTIR within 10 % (Selimovic et al, 2017; Table S8). Additionally, it has been shown that the FTIR fire-integrated emission factors derived for hydroxyacetone are in excellent agreement with that reported for real wildfires by Liu et al (2017b;Selimovic et al, 2017).…”
Section: Comparison With Op-ftirsupporting
confidence: 72%
See 1 more Smart Citation
“…Many of the above species have EFs that agree between PTR-ToF and FTIR within 10 % (Selimovic et al, 2017; Table S8). Additionally, it has been shown that the FTIR fire-integrated emission factors derived for hydroxyacetone are in excellent agreement with that reported for real wildfires by Liu et al (2017b;Selimovic et al, 2017).…”
Section: Comparison With Op-ftirsupporting
confidence: 72%
“…6). The ER to CO are likely the easiest way to incorporate this new NMOG data into models since CO emissions from wildfires are relatively well characterized (Liu et al, 2017b). The 156 PTR ions for which we have identified the NMOG contributors account for a significant fraction of the instrument signal and total NMOG detected by the PTR-ToF instrument in each fire.…”
Section: Emission Factors Emission Ratios and Emission Chemistrymentioning
confidence: 99%
“…Specifically, Liu et al (2017) reported MCE values from three different California wildfires and total organic aerosol (OA) particle EFs, which are the most equivalent to total I/SVOC EFs measured here (though at MCE values of <0.8, we observed higher IVOCs mass loadings in our 20 chromatograms which would likely not be included in the OA EFs at lower particle mass loadings (May et al, 2013) cannot be evaluated at this time. Without this information, uncertainty in using the reported regression models in predicting EFs of various chemical families is estimated to be a factor of 3.…”
Section: /22mentioning
confidence: 74%
“…These regression models can be used to approximate EFs of I/SVOCs or their chemical families from average MCE of real wildfires. For example, comparison with Liu et al (2017) shows the estimated 25 particulate organics from the regression model to be within a factor of 2-3 from those measured in that study. The comparison between predicted and previously measured EFs is affected by methodology, concentration regime, and the definitions of I/SVOC.…”
Section: /22mentioning
confidence: 99%
See 1 more Smart Citation